2014
DOI: 10.1186/1471-2458-14-729
|View full text |Cite
|
Sign up to set email alerts
|

The association between obesity and blood pressure in Thai public school children

Abstract: BackgroundThe prevalence of obesity has substantially increased in the past 3 decades in both developed and developing countries and may lead to an increase in high blood pressure (BP) at an early age. This study aimed to determine the prevalence of obesity and its association with blood pressure among primary school children in central Thailand.MethodsA cross-sectional study was conducted in two public schools in Bangkok in 2012. A total of 693 students (317 boys and 376 girls) aged 8–12 years participated vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 31 publications
3
21
1
6
Order By: Relevance
“…This observation is in agreement with Fishbein in the United States (35). Additionally, the alterations found in the profile of lipoproteins is also in accordance with Skhonthachit P et al in Thai children (36) and with Boyd GS et al (37), who both found a high prevalence of dyslipidemia in overweight and obese children and adolescents. The existence of dyslipidemia is often reported in the many studies that have provided evidence of the association between obesity and the risk of cardiovascular disease.…”
Section: Discussionsupporting
confidence: 72%
“…This observation is in agreement with Fishbein in the United States (35). Additionally, the alterations found in the profile of lipoproteins is also in accordance with Skhonthachit P et al in Thai children (36) and with Boyd GS et al (37), who both found a high prevalence of dyslipidemia in overweight and obese children and adolescents. The existence of dyslipidemia is often reported in the many studies that have provided evidence of the association between obesity and the risk of cardiovascular disease.…”
Section: Discussionsupporting
confidence: 72%
“…4 In Thailand, 17.6% of obese/overweight children presented with metabolic syndrome, 8 while among obese children, 4.7% of boys and 3.2% of girls had hypertension. 9 The prevalence of dyslipidemia in school-age children was 11.8%, with overweight as the sole risk factor.10 Therefore, early identification of children at high risk for obesity should be a pivotal aspect of any obesity prevention initiative. …”
mentioning
confidence: 99%
“…Such factors contribute not only to the accumulation of body fat but also to the development of numerous disorders, and chronic and degenerative diseases, such as diabetes, high blood pressure, dyslipidemia, and cardiopathy 5 . Even though food intake and level of physical activity have not been controlled for in the study sample, there is plenty of evidence in the literature that an inappropriate diet is specifically associated with better socioeconomic status, being one of the causes of weight gain 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional status of children and adolescents has been the target of numerous Brazilian 1-4 and international [5][6][7][8] studies. These data are critical because of the influence of underweight and excess weight (overweight and obesity) on the risk of early-onset metabolic disorders and chronic noncommunicable diseases 1,3 .…”
Section: Introductionmentioning
confidence: 99%